Deposit insurance, market discipline and bank risk - Alexei Karas; William Pyle; Koen Schoors (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
Using evidence from Russia, we explore the effect of the introduction of deposit insurance on bank risk. Drawing on within-bank variation in the ratio of firm deposits to total household and firm deposits, so as to capture the magnitude of the decrease in market discipline after the introduction of deposit insurance, we demonstrate for private, domestic banks that larger declines in market discipline generate larger increases in traditional measures of risk. These results hold in a difference-in-difference setting in which state and foreign-owned banks, whose deposit insurance regime does not change, serve as a control.
URN:NBN:fi:bof-201907021280
Keywords: E65; G21; G28; P34; 330; deposit insurance; market discipline; moral hazard; risk taking; banks; Russia